Delineation of Quaternary Aquifers by Using Long 2D Imaging in Southern Al-Shihaby Area (Wasit Governorate), Eastern Iraq - M. Thabit, Jassim; A.AL-Tamimi, Kassim (Iraqi Journal of Science, 2023)
An electrical survey was carried out by using 2D imaging technique at (15)station. The study area is located southern Al-Shihaby area, south-east of Wasitgovernorate, Eastern Iraq. The numbers of the employed electrodes were (120) andthe (a) spacing equal to (10m), and the total length of survey line is (1200m). Theinverse models of 2D imaging showed one Quaternary aquifer located in theQuaternary deposits which comprises in alluvial fan and wind deposits of(Pleistocene – Holocene) ages. Layers of aquifer consist of gravel and sand withlittle silt. Low resistivity values reflected the presence of clay layers, and increasingsalinity of water gradually with the depth. The aquifer occurs at minimum depthequal to (12m) approximately in the inverse model of 2DSh10 station and maximumdepth equals to (153m) approximately in 2DSh2 station. In addition, the minimumthickness of aquifer was (7m) approximately as appeared in 2DSh15 station and thethickness increased to (91m) approximately in 2DSh4 station. The results indicatedthat the type of aquifer is unconfined.